Das GATS und die EU: Auswirkungen auf Arbeitsmärkte und Regulierungskapazität. 2012 - Kemekliene, Gintare; Watt, Andrew; Rietzler, Katja (Brussels, 2012)
"This study, which was funded by a grant from the Hans Böckler Foundation, addresses actual and expected impacts of the General Agreement on Trade in Services (GATS) on both European labour markets and governments’ regulatory capacity. As such it touches on a number of crucial issues that have been at the centre of debate and controversy in recent years. The study constructs own indicators for the degree of opening of labour markets under the GATS for each EU Member State. These are then used to make a qualitative and quantitative assessment of the actual and expected impact of cross border services trade under both Mode 3 and Mode 4 of the GATS framework. On basis of this analysis, the authors reflect on possible policy responses by national governments, trade unions and other social actors. "